Emergent Mid‐Infrared Nonlinear Optical Candidates With Targeted Balance Performances - Huang, Junben; Abudurusuli, Ailijiang; Yang, Zhihua; Pan, Shilie (Small (Weinheim an der Bergstrasse, Germany), 2025)
Infrared nonlinear optical (NLO) crystal materials exert a crucial role in laser technology, which is extensively utilized in the fields of medical laser, long‐distance laser communication, infrared laser guidance, etc. Currently, the commercially available infrared NLO crystals are diamond‐like structural crystals AgGaQ2 (Q = S, Se) and ZnGeP2. However, their applications are significantly limited owing to their inherent drawbacks, such as low laser damage thresholds and narrow band gaps. Therefore, exploring novel infrared NLO materials with excellent performances is urgent. At present, candidate systems for exploring infrared NLO materials mainly are chalcogenides, pnictides, metal halides for popular systems, and chalcohalides, oxyhalides, heavy metal oxides, oxychalcogenides, nitrides for emergent systems. Notably, among them, pnictides generally exhibited a stronger NLO performance than other systems, but a narrower band gap. Accordingly, after the detailed literature survey, to the best knowledge, ≈139 compounds achieve balanced performances (Eg ≥ 3.0 eV, dij ≥ 0.5 × AgGaS2) in the remaining systems, in which there are 2 metal halides, 9 oxyhalides, 10 heavy metal oxides, 17 nitrides, 19 oxychalcogenides, 22 chalcohalides, and 60 chalcogenides. Thus, the structure‐property survey of these compounds produces the practical design strategy to explore emergent infrared NLO crystal materials with balanced properties. Summarized the systems of research utilized in recent years to explore infrared nonlinear optical materials, which includes chalcogenides, metal halides, oxyhalides, heavy metal oxides, oxychalcogenides, chalcohalides, and nitrides. Remarkably, nitrides as an emergent infrared NLO candidate with wide band gap, large NLO coefficients, and high thermal conductivity deserve further study.